Bacterial Profile in Urine Culture and Amikacin Sensitivity and Emergence of Carbapenem-Resistant Pathogens in Tertiary Medical College Hospital, Bangladesh (KYAMC Journal, 2024)
Background: Urinary tract infection (UTI) is one of the most common encounters both in the outpatient department and inpatient department. It is important to know the bacteriological etiology according to urine culture and to know the antibiotic sensitivity. Objective: Our study was carried out to observe the urine culture and sensitivity pattern to commonly used injectable antibiotics such as amikacin and to look for the emergence of carbapenem-resistant uropathogens.Materials and methods: A total of 150 patients of UTI being culture-positive were isolated and identified by random selection. Samples were collected throughout January 2022 to March 2022. Standard microbiological techniques were used to identify the bacteria and test for susceptibility to various antibiotics. Data were entered into MS Office Excel 2016 for analysis and visualization.Results: The most common urine culture positive was E. coli, 108 (72%) followed by Pseudomonas sp., 16 (11%) and staphylococcus saprophyticus, 15 (10%). The rest of 7% urine culture was positive were other bacterial species. Around 90% of the total cultured E. coli was sensitive to amikacin. Staphylococcus saprophyticus 8 cases (53%), E. coli 15 cases (14%) and Pseudomonas sp. single cases (6%) were resistant to carbapenem. Resistance to vancomycin was common among most of the pathogens, with 88 cases (81%) of E. coli and 12 cases (75%) of Pseudomonas sp. being resistant. In contrast, Staphylococcus saprophyticus had a higher sensitivity to vancomycin, with only 3 cases (20%) being resistant and 12 cases (80%) being sensitive.Conclusion: The study focused on the commonest uropathogens causing UTI and antibiotic resistance in urine isolates may be useful guidelines for clinicians initiating empirical antibiotic therapy as well as help in the formulation of antibiotic therapy strategy.KYAMC Journal Volume: 15, No: 01, April 2024: 16-19.